IMPLEMENTASI ALAT PERMAINAN EDUKATIF BERBASIS BAHAN LINGKUNGAN DALAM MENGEMBANGKAN KOGNITIF ANAK USIA DINI PADA KELOMPOK B DI TK AL-IHSAN OMBEN KABUPATEN SAMPANG - Arifatul Husna; Denok Dwi Anggraini (STPI Bina Insan Mulia Yogyakarta, 2025)
This research examines the implementation of Educational Play Tools (APE) based on environmental materials in the cognitive development of group B children at Al-Ihsan Omben Kindergarten. Teachers often forget the true function of APE and purchase tools that don't match themes, making them unusable again. Using a descriptive qualitative method with data collection techniques through observation, interviews, and documentation from the principal and teachers. Data analysis used data reduction, data presentation, and conclusions. Data validity employed observation persistence and triangulation. Research results show that APE based on environmental materials effectively develops children's cognitive abilities. The materials used are easily found and create interesting learning experiences while encouraging children's active participation. Parents are also beginning to understand that children's education is not limited to reading and writing. Supporting factors for APE implementation include adequate resource availability and awareness of environmental education importance. Meanwhile, inhibiting factors include teachers' limited skills in processing used materials into attractive APE, and negative views regarding used materials. It's important for teachers to ensure the safety of materials used. This research is expected to be a reference for educators and parents to optimize early childhood learning.